Spatial coordination in public good allocation: Nonparametric evidence from decentralized Indonesia - Yamauchi, Futoshi; Chowdhury, Shyamal; Dewina, Reno (International Food Policy Research Institute, 2007)
This paper examines dynamics in public good accessibility and cross-community inequality in Indonesia, using village-level panel data from 2000 to 2006 from their decentralized public-good allocation system. The introduction of decentralization makes public-good investment dependent on initial local income and endowment, and makes it difficult to coordinate investment decisions across communities. Our analysis also shows that possible strategic interactions among communities connected with transportation infrastructure (externalities) implies spatial divergence. Empirical evidence on education and heath facilities, however, demonstrates that during the decentralized period, (1) accessibility to school has improved and school investments were effectively coordinated over space; (2) hospital access has improved only marginally; but (3) per-capita availability of schools and local medical clinics (puskesmas) in the community shows convergence toward low-level equilibria. Despite the coordination in spatial allocation even in the decentralization period (observed in intervillage accessibility), endogenous population mobility and growth partially cancel the benefits of the coordinated efforts in public-good allocation. This point requires further policy attention.